SAFETY AND EFFICACY OF STREPTOKINASE, RETEPLASE AND TENECTEPLASE IN PATIENTS WITH ACUTE STELEVATEDMYOCARDIAL INFARCTION IN AN INTENSIVE CARDIAC CARE UNIT OF A TERTIARY CARE TEACHING HOSPITAL - RANAKISHORE PELLURI; VANITHA RANI N; M. RAMESH; G. KANNAN; P. THENNARASU (International Journal of Pharma and Bio Sciences, 2014)
Although streptokinase and tissue plasminogen activators tenecteplase, reteplase and alteplase are in clinical use for Acute ST-segment elevated myocardial infarction (STEMI), their efficacy in reducing mortality and safety remains less explored. A study was conducted in 90 patients of either sex (30 patients each in streptokinase (SK), tenecteplase (TNK) and reteplase (RTP) groups), aged above 18 years, admitted with acute STEMI in the Intensive Coronary Care Unit to assess the efficacy and safety of fibrinolytics. Data on efficacy and safety parameters before and after the initiation of therapy were obtained from patient medical records and were assessed. Based on the efficacy parameters, 27 patients in SK and RTP group each and 26 in TNP group had more than 50 % resolution; no early peaking in 3 patients each in SK and RTP & one in TNK group; reperfusion arrhythmia was noted in one patient each in SK & TNK; but no arrhythmias in RTP group; symptoms relief < 50% in 5 patients in TNK; 2 in SK & one in RTP treated group; re-MI in one patient in TNK group. Based on the safety parameters, one patient each developed anaphylaxis and hypotension in the SK group, one had CVA in TNK group and no ADRs were identified in RTP group; survival rate was 100% in RTP group and 96.7 % in SK and TNK groups each. The above study identified reteplase as more safe and efficacious than Streptokinase and Tenecteplase.